Augmentation of microbial fuel cell and photocatalytic polishing technique for the treatment of hazardous dimethyl phthalate containing wastewater - Sumaya, Sarmin; Tarek, Mostafa; Selvaraj Mohana, Roopan; Chin, Kui Cheng; Khan, Maksudur R. (Elsevier Ltd, 2021)
In the present paper, the potentiality of integrating microbial fuel cells (MFCs) with a photocatalytic reactor to maximize the wastewater treatment efficiency with concurrent power generation was explored. Dimethyl phthalate (DMP) and acetic acid (AA) were the employed substrate and the co-substrate, respectively, using Pseudomonas aeruginosa as a biocatalyst. MFCs operated by single substrate showed the maximum power generation of 0.75–3.84 W m−3 whereas an addition of AA as the co-substrate yielded 3–12 fold higher power generation. Pseudomonas aeruginosa produced phenazine-1-carboxylic acid in DMP-fed MFC as the metabolite whereas AA along with DMP yielded pyocyanin which reduced the charge transfer resistance. Chemical oxygen demand (COD) removal efficiency in the MFCs was circa 62% after 11 days of operation. Thereafter, it further increased albeit with a drastic reduction in power generation. Subsequently, the MFC anolyte was treated in a photocatalytic reactor under visible light irradiation and catalyzed by CuO-gC3N4. The performance of photocatalytic reactor was evaluated, with COD and total organic carbon (TOC) removal efficiency of 88% and 86% after 200 min of light irradiation. The present work suggests that the MFC can be integrated with photocatalysis as a sustainable wastewater treatment method with concurrent power generation.